Understanding organisational and nursing behaviour changes associated with a therapeutic engagement improvement tool in acute mental health inpatient settings: A qualitative analysis - Francesca Taylor; Sarah Galloway; Kris Irons; Lorna Mess; Laura Pemberton; Karen Worton; Mary Chambers (Elsevier, 2024)
Background: Enhancing the quality of therapeutic engagement between nurse and service user is related to positive impact on care, safety, and recovery outcomes. Achieving improved therapeutic engagement remains challenging in the acute mental health inpatient setting, characterised by complex social processes and contextual features that constrain behaviour change. The Therapeutic Engagement Questionnaire is an evidence-based tool co-produced with service users and nurses to improve therapeutic engagement. Objectives: The objectives of this quality improvement project were to identify the organisational and nursing behaviour changes associated with the Therapeutic Engagement Questionnaire and to understand the active behaviour change ingredients of the improvement tool and how they exert their influence. Design: A qualitative multi-site case study design in which data were collected from study site field notes and document review. Setting: Four acute mental health inpatient case study sites in England. Methods: Data referencing Therapeutic Engagement Questionnaire-linked behaviour change in project meeting field notes and documents from each study site were analysed using an inductive and deductive approach with thematic analysis. The Capability Opportunity Motivation-Behaviour model was employed as a theoretical framework. Findings: The therapeutic engagement tool had the capacity to prompt behaviour change across all three components of the behaviour change model: Capability - through nurses sharing good therapeutic engagement practice and use of statements in the questionnaire to build nurses' knowledge and skills; Opportunity - through organisational barriers being addressed and ward-level practice and culture changes; Motivation - through nurses' awareness of their influence on service user recovery, nurses' alertness to their therapeutic work, and connections between the therapeutic engagement tool and nursing core values. However, the tool did not accord with the values of some nurses, reported to be unmotivated by the recognition it gave their profession for contribution to service user recovery. In sites evidencing more prominent behaviour change, senior leader and ward-level agents of change played a valuable facilitative role. Conclusion: The therapeutic engagement tool had the potential to prompt behaviour changes at organisation and ward level and to the ways individual nurses therapeutically engage with service users, helping strengthen therapeutic engagement practice. Leadership at senior organisational and ward level was important to address contextual barriers to change. The project resulted in a conceptual framework to explain and understand the behaviour change techniques and functions linked to the therapeutic engagement tool. Longevity of the behaviour changes and their impact on service user quality of care requires future evaluation. Tweetable abstract: A therapeutic engagement tool can prompt organisational and nursing behaviour change in acute mental health inpatient settings.